Factors affecting customer preferences in Islamic banking products and services / Nur Hidayah Mohd Rusli - Mohd Rusli, Nur Hidayah (Faculty of Business and Management, 2014)
Nowadays, people and their knowledge have become more significant nowadays, financial is getting more important and they manage it through selected banking system. This study investigate the relationship between product features, service quality, financial strength and soundness, and price to the factor affecting customer preferences in Islamic banking products and services. The respondents of this research are staff in SAJ Holdings Sdn. Bnd. which are participated by 100 respondents. The theoretical framework discussed the elements of product features, service quality, financial strength and soundness, and price. The findings of the study were analyzed by using the Statistical Package for the Social Science (SPSS). Frequency analysis evaluates personal information that relates to choosing Islamic banking products and services. Most of respondents using Islamic banking as selected banking system. Descriptive statistics investigate the influence of product features, service quality, financial strength and soundness and price towards customer preferences. Price variable has less relationship towards customer preferences through the lowest mean. Pearson correlation determines the significant of product features, quality, financial strength and soundness and price. All of the variables have significant relationship towards customer preferences in Islamic banking products and services. Regression analysis determines the most important factor that gives more impact towards customer preferences. Regression analysis also shows that overall customer preferences are strongly correlated with all of the independent variable used.